Dynamic single-cell systemic immune responses in immunotherapy-treated early-stage HR+ breast cancer patients - Xiaopeng Sun; Margaret L. Axelrod; Adrienne G. Waks; Jingxin Fu; Molly DiLullo; Eliezer M. Van Allen; Sara M. Tolaney; Elizabeth A. Mittendorf; Yaomin Xu; Justin M. Balko (npj Breast Cancer)
Abstract The limited added benefit of immune checkpoint inhibitors in breast cancer indicates the pressing need to identify biomarkers of response to minimize risk and maximize benefit. We used single cell RNA sequencing and T cell receptor (TCR) sequencing of peripheral blood mononuclear cells (for 28 samples comprising 79,284 cells) to monitor the peripheral immune dynamic of an exploratory cohort of hormone receptor positive breast cancer patients treated with neoadjuvant nab-paclitaxel+pembrolizumab with the ultimate goal of identifying potential peripheral blood predictive biomarkers. In responsive patients, Granzyme B positive (GZMB+) cytotoxic CD8 T cells expanded post-nab-paclitaxel+pembrolizumab, accompanied by rapid changes in TCR clones. In contrast, non-responders’ peripheral T cells may experience terminal exhaustion and are not significantly altered by treatment. In addition, B cell and monocyte-specific interferon response signatures were also associated with response. Our data suggests that peripheral immunological signatures may represent a facile way to monitor dynamic antitumor immune response.